A critical exploring of grade 10 rural learners' experiences and attitudes towards learning mathematics in Acorhoek classrooms, Mpumalanga province - Mbhiza, Hlamulo Wiseman (My University, 2017)
The purpose of this study was to critically explore Grade 10 rural learners’ experiences and attitudes towards learning mathematics in Acornhoek classrooms, Mpumalanga province. The study further sought to understand factors that shape learners’ experiences and attitudes towards learning mathematics. While the widely accepted view of the study of individuals’ attitudes fall in the quantitative research approaches, this study used critical phenomenological qualitative methodology. I should make it clear that I have deliberately used qualitative approaches to critically explore and interrogate learners’ experiences and attitudes towards mathematics and mathematics learning, because interviews and observations of behaviours are some of the methods that can be used to gain insight into individuals’ experiences and attitudes. Semi-structured one-to-one individual interviews and non-participant classroom observations of twelve learners during learning were used in this study. In addition, this study uses Fairclough’s analytical framework of Critical Discourse Analysis and Bronfenbrenner’s Bioecological systems theory as the theoretical framework to give meaning to the information provided by the learners about their learning of mathematics. To date, the dearth of mathematics education research in rural areas and schools has not been able to offer an account of learners’ experiences and attitudes towards mathematics and mathematics learning within rural schools. Thus, this study is the beginning for other researchers to start researching rural learners’ learning in general, specifically the learning of mathematics in ways that pay respect to the dynamic relationships of various factors that shape the experiences and attitudes of learners towards learning mathematics. The findings emerging from the study illustrate that even when learners are taught in the same way in the classroom by the same teacher, their experiences and attitudes towards mathematics and its learning are inevitably different, which resonates with the research ontology for the study, which is constructionism.
A research report submitted in fullfilment of a degree of Master of Education by dissertation Wits school of Education, curriculum studies University of the Witwatersrand, South Africa March 2017
Keywords: Student teaching; Teachers--Training of--South Africa